2020
DOI: 10.1177/0301574220919090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Occlusal Contact Changes During Retention Between Hawley-Type Retainers and Other Retention Appliances: A Systematic Review

Abstract: Background: Achieving adequate and broad occlusal contacts following orthodontic treatment usually is performed during retention phase, and it ensures good intercuspation of posterior teeth and post-treatment stability. Objective: To investigate the changes in occlusal contacts with the use of Hawley-type retainers (Hawley’s and wrap around retainers) and compare them with other retention appliances. Methods: The search included articles that were published until December 2018 in three popular databases. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Systematic reviews comparing the VFRs and HR retainers in terms of cost-effectiveness, patient satisfaction, survival time, and occlusal contacts concluded that there were very few differences between them and high-quality studies are needed to determine which is a better retainer [ 25 , 26 ]. A previous systematic review has reported that the NOCs improved in patients on HRs but there was no difference when compared to other retainers [ 27 ]. Conclusions from that review may not be valid since they included studies that reported only on NOCs but an assessment of area and distribution of occlusal contacts is more important.…”
Section: Reviewmentioning
confidence: 99%
“…Systematic reviews comparing the VFRs and HR retainers in terms of cost-effectiveness, patient satisfaction, survival time, and occlusal contacts concluded that there were very few differences between them and high-quality studies are needed to determine which is a better retainer [ 25 , 26 ]. A previous systematic review has reported that the NOCs improved in patients on HRs but there was no difference when compared to other retainers [ 27 ]. Conclusions from that review may not be valid since they included studies that reported only on NOCs but an assessment of area and distribution of occlusal contacts is more important.…”
Section: Reviewmentioning
confidence: 99%